Legal regulation of the general aviation in Ukraine: problems and prospects of development - Зуєва, Вікторія Олександрівна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This article examines some aspects of regulation of the general aviation in Ukraine. Under the topic the main features and problem of the general aviation Ukraine at the present stage of its development are determined. The article describes the forms of relations of general aviation and the state. The authors analyze the legal framework in this area that gave reason to clarify the concept of general aviation. In particular the area of «general purpose» is specified on the basis of global experience.